VISI TEOLOGIS TOKOH DAN PENOKOHAN TEKS LONTAR AJI MAYA SANDHI - I Nyoman Raka (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
Lontar Aji Maya Sandi is classified as a spoken text. This lontar describes, said, Tattwa, which is conveyed in the form of dialogue between characters. The teacher figure played by Aji Maya Sandhi to four of his students. What is the structure of the character and characterization of the aji maya sandhi text, how do you say, tattwa text is a virtual password? In order to understand the theological vision of the lontar aji maya sandhi text, structural theory is used with a qualitative approach. The results of the study found, the meaning of the speech, tattwa text, lontar aji maya sandhi. A number of tattwa in Aji Maya Sandhi's text, namely, tattwa kandapat, tattwa, death, tattwa, deliverance, punarbawa, and moksa. Conclusion, Lontar Aji Maya sandhi's text with an educational structure, in the form of a dialogue between teacher figures, played by Aji Maya Sandi with four students; discussing a number of words, tattwa as material for dialogue